Diffusely decreased liver attenuation on post-mortem computed tomography: Comparison with ante-mortem computed tomography and autopsy findings. (March 2019) - Ishida, Masanori; Gonoi, Wataru; Shirota, Go; Okuma, Hidemi; Yamazawa, Sho; Hinata, Munetoshi; Hayashi, Akimasa; Fukayama, Masashi; Abe, Osamu
Highlights: Liver attenuation on PMCT was compared with clinical, AMCT and autopsy findings. PMCT may reflect liver pathological change around death. Herein, assessment of decreased liver attenuation on PMCT needed autopsy findings. Abstract: We present two cases of diffusely decreased liver attenuation on post-mortem computed tomography (CT) which is lower than that on ante-mortem CT. Cases include a 37-year-old female whose cause of death was related to myelodysplastic syndrome (Case #1) and an 88-year-old female whose cause of death was related to malignant lymphoma (Case #2). We compared post-mortem CT (PMCT) liver attenuations with those on ante-mortem CT (AMCT). For Case #1, average AMCT values of the right/left liver were 46.1/50.0 Hounsfield Units (HU) 2 days ante-mortem and PMCT values of the right/left liver were 33.9/38.4 HU 3 h post-mortem. For Case #2, average AMCT values were 61.4/54.9 HU 5 days ante-mortem and PMCT values of the right/left liver were 38.2/40.6 HU 2 h post-mortem. In both Case # 1 and #2, decreased liver attenuations were found on PMCT. Further, autopsy revealed diffuse hepatocellular hemorrhage, deficits, and necrosis in Case #1, and liver infiltration of lymphoma in Case #2. These pathological findings were considered to be related to diffusely decreased liver attenuation on PMCT in conjunction with remarkable deterioration of hepatobiliary function before death. The observed decreases in liver attenuation on PMCT may be attributed mainly to hepatic pathological changes just prior to death. PMCT liver attenuation does not necessarily reflect the ante-mortem state some time before death, and it is therefore necessary to be careful when presuming the ante-mortem hepatic pathological conditions from only PMCT. This attenuation change should be taken into account during PMCT interpretation.